Analisis Kebutuhan Transportasi Penyeberangan Pada Lintasan Waipirit-Hunimua - Hanok Mandaku (ARIKA, 2010)
Transportation needs of the crossing to the island of Ambon, Seram Island in path-Hunimua Waipirit since 2005 shows an increasing trend. Based on data from PT. Ferry Indonesia (Persero) Branch Ambon, since 2005 the flow of cargo through the track has experienced an average increase of 2.799% per year for passengers, 11.389% for 2 wheel vehicles, and 10.412% for 4-wheel vehicles. However, this trend is not followed by infrastructure development and operation patterns in anticipation of an imbalance between aspects of the provision and utilization aspects of ferry transport services, so that the average queuing time at Port can reach 3-5 hours. This study examines pedestrian transportation needs and to design the pattern of development by considering the operational and conceptual design of the existing ferry ports. The results showed transportation demand forecasting model for crossing the track Waipirit-Hunimua until 2014 was Y = 273,680.00 + 46,114.80 X for Passengers, Y = 76155.40 + 17381.00 X for Vehicle Wheels 2, Y = 35053.40 + 7191 , 70x for Vehicle Wheels 4. For that, the proposed operational pattern consists of 4 ships that sail the 16 trips per day on 2 lines, with a circulation time of 12 hours per day so the BOR by 50% and load factor can be optimized (reached 97% in 2014). On the ground facilities, the Port Terminal Building Waipirit need to develop an area of 11.43 m2 and the Areal Vehicle Parking area of 519.96 m2. While in port Hunimua, covering an area of 258.43 m2 Terminal Building and Parking Area covering an area of 578.44 m2